Impactos do uso da água residuária de origem doméstica no sistema solo-planta na chapada do Apodi- RN - Morais, Maria Alcilene (Universidade Federal Rural do Semi-Árido, 2014)
The use of wastewater in agricultural production is sustainable alternative environmental point of view, and especially to the economic reality of the semiarid region of Brazil. The objective of this study was to evaluate the impacts when using wastewater from domestic sources in the soil-plant system and nutritional aspects of the cultivation of elephant grass (irrigated with the same effluent. Experiment was developed in the project of land reform settlement Milagre, Apodi in, RN soil samples were collected in two areas of 150 m2 each, located in a yellow red Ultisol was chosen an area of native forest to savanna hyperxerophilic absent from effluent discharge, serving as a reference; and a cultivated with elephant grass furrow irrigated with treated wastewater. area sampling for soil evaluation occurred during the dry period and after the rainy season. for each period, 79 single soil samples were collected, 24 of the ridge cultivation and 55 in irrigation furrows. samples were collected at depths of 0-20 cm and 20-40 cm and 0-10 cm, 10-20 cm, 20-40 cm, 40-60 cm and 60-80 cm respectively, serving to prepare composite samples. In the native area adopted the procedure of simple random collection totaling 20 samples at 0-10 cm, 10-20 cm, 20-40 cm, 40-60 cm and 60-80 cm. To evaluate the physical-chemical and biological indicators. Thus, the pH and the concentrations of total nitrogen, phosphorus, potassium, calcium and magnesium; population levels of total and fecal coliforms; salmonella, as well as the levels of heavy metals (Mn, Fe, Zn, Cu, Ni and Pb) and organic matter. Wastewater samples were collected for determination of pH, electrical conductivity, biochemical oxygen demand, chemical oxygen demand; total and fecal coliform and salmonella. Samples for assessment of the plant were collected at 60 days for chemical analysis. It was observed that the soil chemical indicators have changed significantly. As the quality of material can be observed that the concentrations of neutral detergent insoluble protein and insoluble protein, acid detergent, showed values 4.47 and 1.60% respectively, indicating a percentage of 11.87% of protein forage, There was presence of total coliform and tolerant terms and absence of salmonella for both the soil and the water
Impacts of the use of wastewater from domestic sources in the soil-plant system on the plateau of the Apodi-RN
Keywords: soil; Water reuse; sanitation; semiarid; Solo; Reuso da água; Saneamento; Semiárido; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO